Personalized Assessment of Anxiety and Avoidance in Children and Their Parents—Development and Evaluation of the Anxiety and Avoidance Scale for Children - Lippert, Michael W.; Sommer, Katharina; Flasinski, Tabea; Pflug, Verena; Rölver, Angela; Christiansen, Hanna; In-Albon, Tina; Knappe, Susanne; Romanos, Marcel; Tuschen-Caffier, Brunna; Schneider, Silvia (Frontiers in Psychology, 2021)
In treating childhood anxiety disorders, therapists use highly individualized anxiety hierarchies to assess anxiety-eliciting situations and to personalize treatment. In contrast, psychometric assessment of anxiety symptoms in children usually consists of standardized questionnaires, assessing either total anxiety or disorder-specific symptom scores, prioritizing comparability over individual information. To account for interindividual differences, the Anxiety and Avoidance Scale for Children (AVAC) was developed, following a precise, personalized, assessment approach. In responding to the questionnaire, children and parents identify the most anxiety-eliciting situations before starting treatment, and rate them for anxiety and avoidance. Ratings are repeated over the course of treatment. The aim of this study is to introduce the new questionnaire and present first data on psychometric properties. The AVAC was administered to 389 children with separation anxiety disorder (N = 148), social anxiety disorder (N = 110) or specific phobia (N = 131) aged 8 to 16 and their parents, along with other measures of anxiety and psychopathology before and after cognitive behavioral treatment. Results showed adequate to good test-retest reliability. The AVAC items correlated significantly with established anxiety questionnaires, indicating convergent construct validity. Regarding divergent construct validity, the AVAC showed only small correlations with externalizing symptoms, demonstrating its precision in measuring anxiety and avoidance. The questionnaire was also sensitive to change after treatment, with medium to large effects in the reduction of anxiety and avoidance. The present analyses suggest that the new personalized assessment approach with the AVAC is a reliable and valid assessment of individualized anxiety and avoidance, as well as change in those constructs over the course of CBT treatment.